Perancangan Sistem Antrian Pelayanan Pasien Pada Puskesmas Cibadak Dengan Metode Multi Channel Single Phase - Dudih Gustian; Salsa Lisna Audina (LPPM STIKOM Tunas Bangsa, 2023)
The Cibadak Health Center is a health service center located in RW 017, Cibadak Village, precisely behind the Cibadak District Office. This Puskesmas has three services, namely General, Maternal and Child Health, and Dentistry. The poor quality of the service process affects the patient, so that the patient is not interested in returning to treatment. According to data from the Cibadak Health Center, the number of patients from June 2021 to May 2022 has decreased. The decrease in the number of patients is because the registration section still uses manuals or still uses paper and there is no computerized system. This queuing problem is one of the causes of competition between service providers so that if the medical service is good, the patient will be interested in returning to the service. This study uses Operations Research techniques with the Multi Channel Single Phase method, a form of queue with two or more queues and one server. The data taken is primary data that calculates the patient's arrival time, the start and completion of procedures that occur at the Cibadak Health Center. This study provides a solution for the Cibadak Health Center to simplify and not delay the required registration time by knowing the queue system of the Cibadak Health Center and determining the optimal service.